IDDF2019-ABS-0225 lncRNA w01880 is downregulated in gastric cancer cell and inhibited proliferation and metastasis. (7th June 2019) - Song, Haojun; Wang, Bujiang; Ding, Xiaoyun
Abstract : Background: Gastric cancer (GC) is one of the common cancers in China, and its pathogenesis is still unknown. Recent studies have reported that long non-coding RNAs (lncRNAs) are important regulators of GC. However, the role and mechanism of lncRNAs in GC are poorly understood. In this study, we characterized a novel lncRNA termed w01880 in GC tissues and cell lines. Methods: We used reverse transcription-quantitative polymerase chain reaction (RT-qPCR) to assayed w01880 levels in GC tissues and cell lines. Lentiviral vector was used to manipulate the expression of w01880 (IDDF2019-ABS-0225 Figure 1C ). Biological functions of w01880 were analyzed using Cell Counting Kit-8 (CCK-8) and Wound Healing in vitro. Results: We analyzed a cohort of 64 patients and found that w01880 was significantly down-expressed in GC tissues compared with paired adjacent normal tissues ((figure 1A ), P <0.001). Combined with clinicopathological features, the expression level of w01880 in GC patients was correlated with depth of invasion, lymph node metastasis and TNM staging ((table 1 ), P <0.05). Then, we found that w01880 is almost low expression in GC cell lines ((figure 1B ), P <0.05). The in vitro overexpression of w01880 inhibited the proliferation and Invasion of GC cell (MNK-45) ((figure 1D, E ), P <0.001). Conclusions: Our data suggested that w01880 functioned as a tumor suppressor lncRNA in GC, which provided a potential biomarker and therapeutic target for GC.